Symptoms of the suicide crisis syndrome and associated risk factors in an acute psychiatric population, a cross-sectional study - Linde Melby; Karina Høyen; Astrid Prestmo; Arne Vaaler; Tuva Kvithyld; Igor Galynker; Fredrik Walby; Mette Langaas; Terje Torgersen (European Psychiatry, 2025)
Abstract Background The focus of suicide research changes from traditional risk factors to acute warning signs. Patient self-reported suicidal ideation (SI) is not a reliable measure of acute suicide risk. Presuicidal syndromes such as suicide crisis syndrome (SCS) attempt to describe measurable syndromes based on warning signs other than SI.